Towards a Practical Setup for Hydrogen Production from Formic Acid. Issue 7 (11th June 2013) - Sponholz, Peter; Mellmann, Dörthe; Junge, Henrik; Beller, Matthias
<x xml:space="preserve">Abstract</x> Formic acid cracker: A mini plant that allows for continuous formic acid decomposition to hydrogen and carbon dioxide under ambient conditions is presented. By using an in situ‐formed ruthenium catalyst, unprecedented turnover numbers over 1 000 000 are achieved. The active catalyst is formed in situ from commercially available [RuCl2(benzene)]2 and 1, 2‐bisdiphenylphosphinoethane.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>